THE ROLE OF MULTIDRUG RESISTANCE ASSOCIATED PROTEIN (MRP) IN THE BLOOD-BRAIN BARRIER AND OPIOID ANALGESIA - Su, Wendy (2013)
The blood brain barrier protects the brain from circulating compounds and drugs. The ATP-binding cassette (ABC) transporter P-glycoprotein (Pgp) is involved with the barrier, both preventing the influx of agent from the blood into the brain and facilitating the efflux of compounds from the brain into the blood, raising the possibility of a similar role for other transporters. Multidrug resistance associated protein (MRP), a 190 kDa protein similar to Pgp is also ABC transport that has been implicated in the blood brain barrier. The current study explores its role in opioid action. Immunohistochemically, it is localized in the choroid plexus in ratsand can be selectively downregulated by antisense treatment at both the level of mRNA, as shown by RT-PCR, and protein, as demonstrated immunohistochemically. Behaviorally, downregulation of MRP significantly enhances the analgesic potency of systemic morphine in MRP knockout mice and in antisense-treated rats by lowering the blood brain barrier. Following intracerebroventricular administration, a number of compounds, including some opioids, are rapidly secreted from the brain into the blood where they contribute to the overall analgesic effects by activating peripheral systems. MRP plays a role in this efflux. Downregulating MRP expression leads to a corresponding decrease in the transport and a diminished analgesic response from opioids administered intracerebroventricularly. Thus, the transporter protein MRP plays a role in maintaining the blood-brain barrier and modulates the activity of opioids.